Bariatric Surgery and Type 1 Diabetes: Unanswered Questions - Korakas, Emmanouil; Kountouri, Aikaterini; Raptis, Athanasios; Kokkinos, Alexander; Lambadiari, Vaia (Frontiers in Endocrinology, 2020)
In recent decades there has been an alarming increase in the prevalence of obesity in patients with type 1 diabetes leading to the development of insulin resistance and cardiometabolic complications, with mechanisms poorly clarified. While bariatric surgery has long been considered an effective treatment option for patients with type 2 diabetes, the evidence regarding its benefits on weight loss and the prevention of complications in T1DM patients is scarce, with controversial outcomes. Bariatric surgery has been associated with a significant reduction in daily insulin requirement, along with a considerable reduction in body mass index, results which were sustained in the long term. Furthermore, studies suggest that bariatric surgery in type 1 diabetes results in the improvement of comorbidities related to obesity including hypertension and dyslipidemia. However, regarding glycemic control, the reduction of mean glycosylated hemoglobin was modest or statistically insignificant in most studies. The reasons for these results are yet to be elucidated; possible explanations include preservation of beta cell mass and increased residual function post-surgery, improvement in insulin action, altered GLP-1 function, timing of surgery and association with residual islet cell mass. A number of concerns regarding safety issues have arisen due to the reporting of peri-operative and post-operative adverse events. The most significant complications are metabolic and include diabetic ketoacidosis, severe hypoglycemia and glucose fluctuations. Further prospective clinical studies are required to provide evidence for the effect of bariatric surgery on T1DM patients. The results may offer a better knowledge for the selection of diabetic patients that will be benefit more from a metabolic surgery.